2015
DOI: 10.1021/jf5058588
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activity and Mechanism of Photoirradiated Polyphenols against Gram-Positive and -Negative Bacteria

Abstract: The bactericidal effect of various types of photoirradiated polyphenols against Gram-positive and -negative bacteria was evaluated in relation to the mode of action. Gram-positive bacteria (Enterococcus faecalis, Staphylococcus aureus, and Streptococcus mutans) and Gram-negative bacteria (Aggregatibacter actinomycetemcomitans, Escherichia coli, and Pseudomonas aeruginosa) suspended in a 1 mg/mL polyphenol aqueous solution (caffeic acid, gallic acid, chlorogenic acid, epigallocatechin, epigallocatechin gallate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 33 publications
5
91
0
Order By: Relevance
“…Recently, Nakamura et al discovered the synergistic effect between aBL and polyphenols, which are naturally occurring polyphenolic compounds in fruits, nuts, and flowers (Nakamura et al, 2015; Nakamura et al, 2012). The polyphenols tested include caffeic acid, gallic acid, chlorogenic acid, epigallocatechin, epigallocatechin gallate, and proanthocyanidin.…”
Section: Synergism Of Antimicrobial Blue Light With Other Agentsmentioning
confidence: 99%
“…Recently, Nakamura et al discovered the synergistic effect between aBL and polyphenols, which are naturally occurring polyphenolic compounds in fruits, nuts, and flowers (Nakamura et al, 2015; Nakamura et al, 2012). The polyphenols tested include caffeic acid, gallic acid, chlorogenic acid, epigallocatechin, epigallocatechin gallate, and proanthocyanidin.…”
Section: Synergism Of Antimicrobial Blue Light With Other Agentsmentioning
confidence: 99%
“…A novel antimicrobial technique based on photo-oxidation of polyphenols has been developed in our laboratory 1316 . Exposing an aqueous solution of polyphenols such as caffeic acid (CA), chlorogenic acid, gallic acid, proanthocyanidin, or crude extract of grape to blue light (wavelength: 400 nm) leads to the photo-oxidation of the polyphenolic hydroxyl group.…”
Section: Introductionmentioning
confidence: 99%
“…This generates hydrogen peroxide (H 2 O 2 ) in the presence of dissolved oxygen 15 . The H 2 O 2 is subsequently photolysed by the same light, resulting in the generation of hydroxyl radicals 13 , which are more potent oxidants than H 2 O 2 17 . When the hydroxyl radicals interact with bacterial cells, they cause lethal oxidative damage such as DNA oxidation and lipid peroxidation 13, 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that an important anticancer mechanism of plant polyphenols is mediated through intracellular copper mobilization and reactive oxygen species (ROS) generation, which is a characteristic feature of pro-oxidant properties of polyphenolic compounds, leading to cancer cell death (Khan et al 2014). In our previous studies, the pro-oxidant potential of polyphenols was applied to the development of a novel disinfection technique (Nakamura et al 2012b(Nakamura et al , 2013(Nakamura et al , 2015. Exposing an aqueous solution of polyphenols to blue light led to photooxidation of the polyphenolic hydroxyl group, resulting in the generation of hydrogen peroxide (H 2 O 2 ) produced via electron transfer from photooxidized polyphenols to dissolved oxygen.…”
Section: Introductionmentioning
confidence: 99%